Training in endoscopic mucosal resection and endoscopic submucosal dissection: Face, content and expert validity of the live porcine model - Küttner-Magalhães, R (2018)
INTRODUCTION: Endoscopic mucosal resection and endoscopic submucosal dissection are demanding procedures. This study aims to establish face, content and expert validity of the live porcine model in performing endoscopic mucosal resection, endoscopic submucosal dissection, complication management and to assess it as a training tool. MATERIAL AND METHODS: Tutors and trainees participating in live porcine model endoscopic mucosal resection and endoscopic submucosal dissection workshops filled out a questionnaire regarding the realism of the model compared to human setting and its role as a learning tool. A 10-point Likert scale was used. RESULTS: Ninety-one endoscopists (13 tutors; 78 trainees) were involved in four workshops. Median global classifications for the realism of the life porcine model ranged between 7.0-8.0 (interquartile range 5.0-9.0). Procedures resembled human cases with a median of 9.0 (8.0-9.0) for oesophageal multiband endoscopic mucosal resection; 8.5 (8.0-9.0) for oesophageal endoscopic submucosal dissection; 9.0 (8.0-10.0) for gastric endoscopic submucosal dissection; and 9.0 (8.5-9.75 and 8.0-9.69) for complication detection and management. The animal model as a learning tool had median scores of 9.0 (7.0-10.0) considering how procedures are performed; 9.0-9.5 (8.0-10.0) for usefulness for beginners; and 9.0-10.0 (5.0-10.0) regarding it a prerequisite. CONCLUSIONS: Training in a live porcine model was considered very realistic compared to the human setting and was highly appreciated as a learning tool. This is the first study to establish face, content and expert validity of the live porcine model in performing multiband endoscopic mucosal resection, oesophageal and gastric endoscopic submucosal dissection. The validation of this model provides the rationale to incorporate it into formal teaching programmes.